GA Houses 177 : 50 Houses from Archive 3 : Japan 2001-2021 - Futagawa, Yoshio; Saito, Hitomi; Nakamura, Akiyo; Sekimoto, Reiko (Tokyo : A.D.A. EDITA Tokyo Co., Ltd., 2021)
Ishiyama, Osamu ; Kishi, Waro ; Saito, Yutaka ; Kitagawara, Atsushi ; Aoki, Jun ; Endoh, Masaki + Ikeda, Masahiro ; Yoneda, Akira + Ikeda, Masahiro ; Nakahigashi, Hisakazu ; Suzuki, Ryoji ; Irie, Kei'ichi + Ikeda, Masahiro ; Ban, Shigeru ; Tokyo Institute of Technology Tsukamoto lab. + Atelier Bow-Wow ; Arima, Hiroyuki ; Sambuichi, Hiroshi ; Maeda, Norisada ; Abe, Ryo ; Ando, Tadao ; Okada, Satoshi ; Endo, Shuhei ; Komada, Takeshi + Komada, Yuka ; Suga, Shotaro ; Nagayama, Yuko ; Miyamoto,; Katsuhiro ; Nishizawa, Ryue ; Tominaga, Hiroko ; Yamashita, Yasuhiro ; Takasago, Masahiro ; Fujimori, Terunobu + Kawakami, Keiichi ; Shiina, Eizo + Umezawa, Ryozo ; Takei, Makoto + Chie Nabeshima/TNA ; Maeda, Keisuke ; Kuma, Kengo ; Seijma, Kazuyo ; Fujimoto, Sou ; Kidosaki, Hirotaka ; Kubota, Katsufumi ; Ichikawa, Sota ; Fuse, Shigeru ; Tanijiri, Makoto + Yoshida, Ai ; Matsuoka, Satoshi + Tamura, Yuki ; Nakagawa, Erika ; Hirata, Akihisa ; Nakayama, Hideyuki ; Shimada, Yo ; Yokogawa, Ken ; Aoki, Koji ; Onishi, Maki + Hyakuda, Yuki ; o+h ; Yamada, Suzuko ; Takeguchi, Kentaro + Yamamoto, Aasako/Alphaville ; Hata, Tomohiro
boek